The influence of newly synthesized tellurium-containing cyanine dyes on the intensity of oxidative processes in the bodies of mammals - A. I. Israpilova; A. M. Dzhafarova; A. A. Adieva; G. M. Abakarov; N. O. Guseynova; U. Y. Khalimbekova; M. D. Astaeva; K. S. Bekshokov (Юг России: экология, развитие, 2024)
The purpose of this work was to study the influence of new synthesized organotellurium compounds (TOCs) on the intensity of oxidative processes in the body of mammals – in this case, the blood and liver of rats.The experiments were performed on white outbred rats, which were given a single dose of various TOC derivatives (0.01 g/kg). The next day, the animals were decapitated, blood was collected and the liver was isolated. The content of products of oxidative modification of lipids and proteins, as well as the low molecular weight antioxidant glutathione, was determined in blood plasma, erythrocytes and liver homogenate.It was found that all TOC derivatives studied significantly increase the intensity of lipid peroxidation in erythrocytes and hepatocytes, as evidenced by a multiple increase in the concentration of malondialdehyde (MDA) in them. At the same time, TOC suppresses the levels of oxidative damage to liver proteins, which is expressed in a significant decrease in the content of carbonyl groups. A study of glutathione content in the rat erythrocytes showed the absence of any significant effects of TOS on this antioxidant in erythrocytes.However, changes in its concentration were found in the liver, which depend on the nature of TOS (for TOS1 and TOS3 a decrease and for TOS2 a slight increase). Newly synthesized TOC demonstrate pronounced prooxidant properties, significantly increasing the intensity of oxidative processes in lipids, which makes them promising agents for antibacterial, antiviral and antitumor therapy.